Dietary Crocin Inhibits Colitis and Colitis-Associated Colorectal Carcinogenesis in Male ICR Mice. (25th December 2012) - Kawabata, Kunihiro; Tung, Nguyen Huu; Shoyama, Yukihiro; Sugie, Shigeyuki; Mori, Takayuki; Tanaka, Takuji
Abstract : A natural carotenoid crocin is contained in saffron and gardenia flowers (crocuses and gardenias) and is used as a food colorant. This study reports the potential inhibitory effects of crocin against inflammation-associated mouse colon carcinogenesis and chemically induced colitis in male ICR mice. In the first experiment, dietary crocin significantly inhibited the development of colonic adenocarcinomas induced by azoxymethane (AOM) and dextran sodium sulfate (DSS) in mice by week 18. Crocin feeding also suppressed the proliferation and immunohistochemical expression of nuclear factor- (NF-) κ B but increased the NF-E2-related factor 2 (Nrf2) expression, in adenocarcinoma cells. In the second experiment, dietary feeding with crocin for 4 weeks was able to inhibit DSS-induced colitis and decrease the mRNA expression of tumor necrosis factor α, interleukin- (IL-) 1 β, IL-6, interferon γ, NF- κ B, cyclooxygenase-2, and inducible nitric oxide synthase in the colorectal mucosa and increased the Nrf2 mRNA expression. Our results suggest that dietary crocin suppresses chemically induced colitis and colitis-related colon carcinogenesis in mice, at least partly by inhibiting inflammation and the mRNA expression of certain proinflammatory cytokines and inducible inflammatory enzymes. Therefore, crocin is a candidate for the prevention of colitis and inflammation-associated colon carcinogenesis.